2019
DOI: 10.3346/jkms.2019.34.e328
|View full text |Cite
|
Sign up to set email alerts
|

Does Cephalosporin Skin Test Predict Immediate Hypersensitivity to Cephalosporin?

Abstract: ► See the article "Results of Intradermal Skin Testing with Cefazolin according to a History of Hypersensitivity to Antibiotics" in volume 34, number 50, e319.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Therefore, in most hospitals in China, especially primary hospitals where medical and pharmaceutical professional skill level are relatively low and training is relatively less, a routine skin test would be carried out before cephalosporin is administered, but whether the routine skin test is required before the use of cephalosporin is controversial. 9,10 Because the metabolites of cephalosporins still cannot be identified clearly and no special-purpose reagents for the skin test are currently available, the sensitivity, specificity, and positive predictive value of the cephalosporin skin test are uncertain. 9,10 In addition, the predictive value of the routine skin test for cephalosporin (RSTC) for immediate allergic reactions is not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in most hospitals in China, especially primary hospitals where medical and pharmaceutical professional skill level are relatively low and training is relatively less, a routine skin test would be carried out before cephalosporin is administered, but whether the routine skin test is required before the use of cephalosporin is controversial. 9,10 Because the metabolites of cephalosporins still cannot be identified clearly and no special-purpose reagents for the skin test are currently available, the sensitivity, specificity, and positive predictive value of the cephalosporin skin test are uncertain. 9,10 In addition, the predictive value of the routine skin test for cephalosporin (RSTC) for immediate allergic reactions is not available.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Because the metabolites of cephalosporins still cannot be identified clearly and no special-purpose reagents for the skin test are currently available, the sensitivity, specificity, and positive predictive value of the cephalosporin skin test are uncertain. 9,10 In addition, the predictive value of the routine skin test for cephalosporin (RSTC) for immediate allergic reactions is not available. 11 Furthermore, the RSTC can evoke an allergic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…19 Furthermore, although patients could have a cephalosporin allergy in the absence of a penicillin allergy, penicillin allergy testing is still commonly utilized in the evaluation of a cephalosporin allergy because cephalosporin testing has neither been well validated nor standardized. 20,21 Thus, penicillin allergy testing remains the recommended intervention 22 in identifying those who could most appropriately benefit from the use of clindamycin for prophylaxis in otolaryngologic surgery. Although previous studies have shown that penicillin allergy testing is cost-saving across various scenarios, 23,24 none have evaluated its economic viability in the specific situation outlined above that is commonly encountered by otolaryngologists in the perioperative period.…”
Section: Introductionmentioning
confidence: 99%
“…Penicillin allergy testing is a reliable and validated diagnostic intervention to identify patients who truly have an IgE‐mediated hypersensitivity reaction to penicillin 19 . Furthermore, although patients could have a cephalosporin allergy in the absence of a penicillin allergy, penicillin allergy testing is still commonly utilized in the evaluation of a cephalosporin allergy because cephalosporin testing has neither been well validated nor standardized 20,21 . Thus, penicillin allergy testing remains the recommended intervention 22 in identifying those who could most appropriately benefit from the use of clindamycin for prophylaxis in otolaryngologic surgery.…”
Section: Introductionmentioning
confidence: 99%